2007
DOI: 10.1063/1.2745321
|View full text |Cite
|
Sign up to set email alerts
|

A strong reduction in the density of near-interface traps at the SiO2∕4H-SiC interface by sodium enhanced oxidation

Abstract: This paper demonstrates how sodium enhanced oxidation of Si face 4H-SiC results in removal of near-interface traps at the SiO2∕4H-SiC interface. These detrimental traps have energy levels close to the SiC conduction band edge and are responsible for low electron inversion channel mobilities (1–10cm2∕Vs) in Si face 4H-SiC metal-oxide-semiconductor field effect transistors. The presence of sodium during oxidation increases the oxidation rate and suppresses formation of these near-interface traps resulting in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…We cannot distinguish between these two possibilities in this experiment but very similar behavior has been observed for thermal oxides on SiC containing sodium ions. 27 This experiment demonstrates two things. First, the net negative charge observed in the Al 2 O 3 layers is not a permanently fixed charge but rather electrons trapped within the oxide which can be released to the SiC using depletion bias and UV exposure.…”
Section: Resultsmentioning
confidence: 82%
“…We cannot distinguish between these two possibilities in this experiment but very similar behavior has been observed for thermal oxides on SiC containing sodium ions. 27 This experiment demonstrates two things. First, the net negative charge observed in the Al 2 O 3 layers is not a permanently fixed charge but rather electrons trapped within the oxide which can be released to the SiC using depletion bias and UV exposure.…”
Section: Resultsmentioning
confidence: 82%
“…However, interface traps were generated at the SiO 2 /SiC interface, which is a disadvantage. The interface traps resulted in reduction of the channel mobility in the SiC metal-oxide-semiconductor field effect transistor (MOSFET) [2,3]. The Si-covered 6H-SiC(0001) surface was transformed from a Si-rich to C-rich one such as (3 × 3), (…”
Section: Introductionmentioning
confidence: 99%
“…† Corresponding author: t-ikari@ube-k.ac.jp on the Si surface with small amounts of oxygen exposure [8,9]. The reduction of the interface traps has been reported with Na-enhanced oxidation of a Si-face 4H-SiC surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, NITs may play a dominant role because they are considered to create trap levels close to the conduction band edge of 4H-SiC at a high density [11][12][13][14]. It has been reported that NITs can be effectively removed by the incorporation of N [15], Na [16], K [17], and P [18] as revealed either by using low-temperature capacitance-voltage (C-V ) [15,18] or thermal dielectric relaxation current (TDRC) [16][17][18] measurements. It is interesting to note that improved field-effect mobilities can be obtained by utilizing oxides incorporating N [3,4], Na [5], and P [6], and thus we can assume that the NIT density is closely related to the field-effect mobility.…”
Section: −1mentioning
confidence: 99%